Roles of the Courts in New Zealand in Giving Effect to International Human Rights - with Some History - Keith, Kenneth J (Victoria University of Wellington Law Review, 1999)
The Right Honourable Sir Kenneth Keith was the fourth speaker at the NZ Institute of International Affairs Seminar. In this article he describes and reflects upon the role of courts and judges in relation to the advancement of human rights, an issue covered in K J Keith (ed) Essays on Human Rights (Sweet and Maxwell, Wellington, 1968). The article is divided into two parts. The first part discusses international lawmakers attempting to protect individual groups of people from 1648 to 1948, including religious minorities and foreign traders, slaves, aboriginal natives, victims of armed conflict, and workers. The second part discusses how from 1945 to 1948, there was a shift in international law to universal protection. The author notes that while treaties are not part of domestic law, they may have a constitutional role, be relevant in determining the common law, give content to the words of a statute, help interpret legislation which is in line with a treaty, help interpret legislation which is designed to give general effect to a treaty (but which is silent on the particular matter), and help interpret and affect the operation of legislation to which the international text has no apparent direct relation.